PENDIDIKAN SENI SEBAGAI ALTERNATIF PENDIDIKAN MULTIKULTURAL (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
Multicultural as one of the art learning approach is essential in one’s character building process in order to own relatively strong personality. Multicultural approach should be flexible depending on the ability of the learner, society, and cultural and social condition of the environment. The multicultural approach learning should emphasize on the development of the sensitivity of feeling, esthetics, and ability to imagine and to create. It implies on the role and competence of the art teachers. Art teacher is demanded to be knowledgeable, skillful, and responsible of his/her profession; to master art, and to be able to develop teaching material; to master the theories and practices in the frame of art learning; to be able to plan and manage art learning. Kata kunci: multikultural, plural, pendidikan seni.